Respuesta :
(a)f(x) + g(x) = 8x + 9 + 2x - 5 = 10x + 4
(b)(f.g)(x) = (8x + 9) (2x - 5)
= 16x - 40 + 18x - 45
= 34x - 85
(c)f(g(x)) = 8(2x - 5) + 9
= 16x - 40 + 9
= 16x - 31
Hope it helped!
(b)(f.g)(x) = (8x + 9) (2x - 5)
= 16x - 40 + 18x - 45
= 34x - 85
(c)f(g(x)) = 8(2x - 5) + 9
= 16x - 40 + 9
= 16x - 31
Hope it helped!
Answer:
Part A - [tex](f+g)(x)=10x+4[/tex]
Part B - [tex](f\cdot g)(x)=16x^2-22x-45[/tex]
Part C - [tex]f[g(x)]=16x-31[/tex]
Step-by-step explanation:
Given : Functions [tex]f(x)=8x+9[/tex] and [tex]g(x)=2x-5[/tex]
To find : Complete the function below :
Part A : (f+g)(x)
As [tex](f+g)(x)=f(x)+g(x)[/tex]
Substitute the value of f(x) and g(x)
[tex](f+g)(x)=8x+9+(2x-5)[/tex]
[tex](f+g)(x)=8x+9+2x-5[/tex]
[tex](f+g)(x)=10x+4[/tex]
Part B : (f ⋅ g)(x)
As [tex](f\cdot g)(x)=f(x)\cdot g(x)[/tex]
Substitute the value of f(x) and g(x)
[tex](f\cdot g)(x)=(8x+9)\cdot (2x-5)[/tex]
[tex](f\cdot g)(x)=8x\times 2x-8x\times 5+9\times 2x-9\times 5[/tex]
[tex](f\cdot g)(x)=16x^2-40x+18x-45[/tex]
[tex](f\cdot g)(x)=16x^2-22x-45[/tex]
Part C : f[g(x)]
f[g(x)] means substitute value of g(x) in place of x in f(x)
[tex]f[g(x)]=f[2x-5][/tex]
[tex]f[g(x)]=8(2x-5)+9[/tex]
[tex]f[g(x)]=16x-40+9[/tex]
[tex]f[g(x)]=16x-31[/tex]